Linked mercury methylation and nitrification across oxic subpolar regions - Despins, Marissa C.; Mason, Robert P.; Aguilar-Islas, Ana M.; Lamborg, Carl H.; Hammerschmidt, Chad R.; Newell, Silvia E. (Frontiers in Environmental Chemistry, 2023)
Methylmercury (MeHg) is a neurotoxin that bioaccumulates to potentially harmful concentrations in Arctic and Sub-Arctic marine predators and those that consume them. Monitoring and modeling MeHg bioaccumulation and biogeochemical cycling in the ocean requires understanding of the mechanisms behind net mercury (Hg) methylation. The key functional gene pair for Hg methylation, hgcAB, is widely distributed throughout ocean basins and spans multiple microbial phyla. While multiple microbially mediated, anaerobic pathways for Hg methylation are known, in the ocean, the majority of hgcA homologs have been found in oxic subsurface waters, in contrast to other ecosystems. In particular, microaerophilic Nitrospina, a genera of nitrite-oxidizing bacteria containing a hgcA-like sequence, have been proposed as a potentially important Hg methylator in the upper ocean. The objective of this work was therefore to examine the potential of nitrifiers as Hg methylators and quantify total Hg and MeHg across three Arctic and Subarctic seas (the Gulf of Alaska, the Bering Sea and the Chukchi Sea) in regions where Nitrospina are likely present. In Spring 2021, samples for Hg analysis were obtained with a trace metal clean rosette across these seas. Mercury methylation rates were quantified in concert with nitrification rates using on-board incubation experiments with additions of stable isotope-labeled Hg and NH4+. A significant correlation between Hg methylation and nitrification was observed across all sites (R2 = 0.34, p < 0.05), with the strongest correlation in the Chukchi Sea (R2 = 0.99, p < 0.001). Nitrospina-specific hgcA-like genes were detected at all sites. This study, linking Hg methylation and nitrification in oxic seawater, furthers understanding of MeHg cycling in these high latitude waters, and the ocean in general. Furthermore, these studies inform predictions of how climate and human interactions could influence MeHg concentrations across the Arctic in the future.